THE INFLUENCE OF OCCUPATIONAL HEALTH AND SAFETY ON EMPLOYEE PRODUCTIVITY IN THE PRODUCTION DEPARTMENT OF PT. EASTERN PEARL FLOUR MILLS MAKASSAR - Nabila Salsabila Suparman; Andi Mustika Amin, Rezky Amalia Hamka, M. Ikhwan Maulana Haeruddin, Anwar (Adisam Publisher, 2025)
This research aims to determine the effect of occupational health and safety on employee productivity in the production department of PT. Eastern Pearl Flour Mills Makassar. This type of research is quantitative research with an associative approach. The data collection method was carried out by distributing questionnaires. The population in this study were all employees of the production department of PT. Eastern Pearl Flour Mills Makassar, totaling 70 people, were also sampled using a sampling technique, namely saturated sampling. The data analysis techniques include the validity test, reliability test, classical assumption test, multiple linear regression test, t test, f test, and R2 test which are aimed at testing the proposed hypothesis. With data processed through the Statistical Product and Service Solution (SPSS) program. The results of this research show that occupational health and safety have a positive and significant effect on employee productivity, both partially and simultaneously. This shows that the higher the level of occupational health and safety of employees in the production department of PT. Eastern Pearl Flour Mills Makassar, the higher the level of employee productivity in the production department of PT. Eastern Pearl Flour Mills Makassar.